Comunicaciones tecnológicas y su aporte en la formación de los profesionales del periodismo - Martillo Mayorga, Jeniffer Michelle (2022)
Technological communication plays an important role in today's society, the same one that has generated computer tools that are used as a contribution to the information of journalism professionals, facilitating the tasks they carry out daily; This research seeks to determine how technological communications contribute to the training of journalism professionals. For the development of the case study, the survey technique was applied, which allowed the use of the qualitative and quantitative method, carrying out a statistical control of the data found, as well as describing in a practical way the vicissitudes that students who are training as professional journalists have in a practical way. knowledge about the various digital tools, concluding that students in their training as journalism professionals have problems in handling certain technological tools such as editing and producing a video, creating digital animations, editing photographs, activities that are basic in the work as communicators of which they must have extensive knowledge of the functions performed by each of them, which affects the development of their skills and strengths as journalistic correspondents.